Profiling the expression and function of oestrogen receptor isoform ER46 in human endometrial tissues and uterine natural killer cells. Issue 3 (28th February 2020) - Gibson, Douglas A; Esnal-Zufiaurre, Arantza; Bajo-Santos, Cristina; Collins, Frances; Critchley, Hilary O D; Saunders, Philippa T K
Abstract: STUDY QUESTION: Does the oestrogen receptor isoform, ER46, contribute to regulation of endometrial function? SUMMARY ANSWER: ER46 is expressed in endometrial tissues, is the predominant ER isoform in first trimester decidua and is localised to the cell membrane of uterine natural killer (uNK) cells where activation of ER46 increases cell motility. WHAT IS KNOWN ALREADY: Oestrogens acting via their cognate receptors are essential regulators of endometrial function and play key roles in establishment of pregnancy. ER46 is a 46-kDa truncated isoform of full length ERα (ER66, encoded by ESR1 ) that contains both ligand- and DNA-binding domains. Expression of ER46 in the human endometrium has not been investigated previously. ER46 is located at the cell membrane of peripheral blood leukocytes and mediates rapid responses to oestrogens. uNK cells are a phenotypically distinct (CD56 bright CD16 − ) population of tissue-resident immune cells that regulate vascular remodelling within the endometrium and decidua. We have shown that oestrogens stimulate rapid increases in uNK cell motility. Previous characterisation of uNK cells suggests they are ER66-negative, but expression of ER46 has not been characterised. We hypothesise that uNK cells express ER46 and that rapid responses to oestrogens are mediated via this receptor. STUDY DESIGN, SIZE, DURATION: This laboratory-based study used primary human endometrial ( n  = 24) and decidual tissue biopsies ( n  = 30) as well as uNK cells which were freshly isolated from first trimester human decidua ( n  = 18). PARTICIPANTS/MATERIALS, SETTING, METHODS: Primary human endometrial and first trimester decidual tissue biopsies were collected using methods approved by the local institutional ethics committee (LREC/05/51104/12 and LREC/10/51402/59). The expression of ERs (ER66, ER46 and ERβ) was assessed by quantitative PCR, western blot and immunohistochemistry. uNK cells were isolated from first-trimester human decidua by magnetic bead sorting. Cell motility of uNK cells was measured by live cell imaging: cells were treated with 17β-oestradiol conjugated to bovine serum albumin (E2-BSA, 10 nM equivalent), the ERβ-selective agonist 2, 3-bis(4-hydroxyphenyl)-propionitrile (DPN; 10 nM) or dimethylsulphoxide vehicle control. MAIN RESULTS AND THE ROLE OF CHANCE: ER46 was detected in proliferative and secretory phase tissues by western blot and was the predominant ER isoform in first-trimester decidua samples. Immunohistochemistry revealed that ER46 was co-localised with ER66 in cell nuclei during the proliferative phase but detected in both the cytoplasm and cell membrane of stromal cells in the secretory phase and in decidua. Triple immunofluorescence staining of decidua tissues identified expression of ER46 in the cell membrane of CD56-positive uNK cells which were otherwise ER66-negative. Profiling of isolated uNK cells confirmed expression of ER46 by quantitative PCR and western blot and localised ER46 protein to the cell membrane by immunocytochemistry. Functional analysis of isolated uNK cells using live cell imaging demonstrated that activation of ER46 with E2-BSA significantly increased uNK cell motility. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Expression pattern in endometrial tissue was only determined using samples from proliferative and secretory phases. Assessment of first trimester decidua samples was from a range of gestational ages, which may have precluded insights into gestation-specific changes in these tissues. Our results are based on in vitro responses of primary human cells and we cannot be certain that similar mechanisms occur in situ . WIDER IMPLICATIONS OF THE FINDINGS: E2 is an essential regulator of reproductive competence. This study provides the first evidence for expression of ER46 in the human endometrium and decidua of early pregnancy. We describe a mechanism for regulating the function of human uNK cells via expression of ER46 and demonstrate that selective targeting with E2-BSA regulates uNK cell motility. These novel findings identify a role for ER46 in the human endometrium and provide unique insight into the importance of membrane-initiated signalling in modulating the impact of E2 on uNK cell function in women. Given the importance of uNK cells to regulating vascular remodelling in early pregnancy and the potential for selective targeting of ER46, this may be an attractive future therapeutic target in the treatment of reproductive disorders. STUDY FUNDING/COMPETING INTEREST(S): These studies were supported by Medical Research Council (MRC) Programme Grants G1100356/1 and MR/N024524/1 to PTKS. H.O.D.C. was supported by MRC grant G1002033. The authors declare no competing interests related to the published work.